Digital generation in the context of predicting the professional future - E. F. Zeer; N. G. Tserkovnikova; V. S. Tretyakova (Образование и наука)
Introduction. The rapid development of information and communication technologies, which penetrate almost all the spheres of life, affects the formation of modern children, adolescents and youth people. The digital information field imposes on people a lifestyle that was not typical of the previous industrial civilisation. There is a need to assess the impact of the rapid spread of information technologies on the younger generation, since the previous methods, forms and educational technologies of working with them are largely outdated and do not give the planned result. It also becomes important to study the phenomenon of the digital generation, taking into account their psychological and pedagogical features in predicting the professional future.The present theoretical research aims to analyse the psychological and pedagogical phenomenological features of representatives of the digital generation in the context of professional education and predicting their professional future.Methodology and research methods. The methodological basis of the research is the concept of personality formation as a natural dependence of mental phenomena on the social factors that generate them. The research was carried out by using theoretical and methodological analysis of scientific literature on the issues of phenomenological features of representatives of the digital generation in the context of professional education and predicting the professional future. The methods of comparison, generalisation, concretisation, heuristic method and psychodiagnostic method were also used in the work.Results. The article presents an analysis of the phenomenon of the digital generation, examines the cultural, historical, psychological and pedagogical features of the digital generation in the context of professional education and predicting the professional future. The authors define the manifestation of these features in the communicative, cognitive, emotional-volitional, motivational-need spheres of the individual, and in relation to himself/herself. The theoretical structure of the prognostic competence of an individual, as well as a model for predicting the professional future, have been elaborated. The results of a pilot research of some components of predictive competence of schoolchildren and students are demonstrated.Scientific novelty. The scientific novelty of the work consists in the enrichment of psychological and pedagogical science knowledge about the phenomenological characteristics of the digital generation in the context of vocational education and predicting the professional future.Practical significance. The identified cultural-historical and psychological-pedagogical features of representatives of the digital generation can be useful to teachers in interacting with that generation in the educational process, personal contact, predicting the professional future of modern youth people, as well as in establishing communication between representatives of different generations in different social groups. The obtained results can be used to develop a new paradigm of information interaction of members of educational process, to introduce and implement conceptual structural-functional model of predicting professional future of the student of the digital generation, to develop and implement new forms and methods of active learning. The research materials will be useful for teachers, psychologists, and social professionals to understand the specific needs of digital generation representatives.